Evaluating consumption and cost savings from new air-conditioner purchases: The case of Singapore. (October 2020) - Liddle, Brantley; Loi, Tian Sheng Allan; Owen, Anthony D.; Tao, Jacqueline
Abstract: Air conditioning (AC) is a major source of household electricity consumption in Singapore and there is evidence that the efficiency of ACs could be improved substantially. Employing 45 months of energy bills and survey data and the Fixed Effects difference-in-differences estimator, we calculated a savings of 7.8% of total energy consumption after the purchase of a more efficient AC compared to an estimated expected savings of 12.6%. This suggests a rebound or take-back of savings around 38.2%. Such a less-than-100% of theoretical savings achieved is in line with other (outside Singapore) estimates and economic/behavioural theory since after purchasing a new AC, households may (i) use a lower temperature setting or (ii) use the AC longer in order to (1) fulfil (previously) unmet demand and/or (2) respond to the effective lower costs of running the AC. Our results have implications for both energy efficiency labelling policies and for Singapore's recently implemented carbon tax. Highlights: We study residential energy savings from more efficient air-conditioners in Singapore. We use energy bills, survey data, and difference-in-difference estimations. A 7.8% savings in total energy consumption is calculated from purchasing a new AC. Compared to expected savings, we estimate a rebound or take-back of 38%.